LEVELS OF REGIONAL PHENOTYPIC ADAPTATION (Q(ST)) INDICATE THAT NEUTRALITY HAS SHAPED THE POPULATION STRUCTURE OF THE SOYBEAN-INFECTING PATHOGEN Rhizoctonia solani AG-1 IA - Ferro, Camila Geovana [UNESP]; Silva, Tatiane Carla [UNESP]; Campos Vicentini, Samara Nunes [UNESP]; Ferrando, Guilherme Moraes [UNESP]; Ceresini, Paulo Cezar [UNESP] (Univ Fed Rural Semi-arido-ufersa, 2020)
Populations of the soybean leaf blight pathogen (Rhizoctonia solani AG-1 IA) are highly genetically differentiated along a latitudinal gradient in the major soybean growing regions of Brazil. However, the evolutionary processes leading to regional adaptation are still unknown. The objective of this study was to evaluate the relative importance of neutral genetic variation and natural selection on the divergence and regional adaptation of populations of the soybean-infecting pathogen R. solani AG-1 IA. Therefore, we compared the phenotypic differentiation in quantitative traits (Q(ST)) and the neutral genetic differentiation (F-ST, based on microsatellites data) among three pairs of populations. As measures of phenotypic responses of the fungus (quantitative traits), we estimated the tolerance to temperature stress and the tolerance to a broadspectrum fungicide (copper oxychloride) under optimal (25 degrees C) and high temperature conditions (33.5 degrees C). In general there was an increase in genetic variance with a positive effect on the heritability for tolerance to copper fungicide under temperature stress. The genetic differences among populations were the main determinants of thermal adaptation in R. solani AG-1 IA (h2 >= 0.70). The analysis of neutral genetic structure (F-ST) indicated subdivision between the three pairs of populations. Although population pairwise comparisons between F-ST and Q(ST) values did not follow a single pattern, the majority of Q(ST) values did not differ significantly from F-ST, indicating that, for the quantitative characters studied, neutrality (or neutral evolution) had a major role in the regional adaptation of R. solani AG-1 IA populations.
Keywords: Q(ST); F-ST; Directional selection; Neutrality; Stabilizing selection